2014
DOI: 10.1038/ni.2991
|View full text |Cite
|
Sign up to set email alerts
|

Emerging functions of the unfolded protein response in immunity

Abstract: The unfolded protein response (UPR) has traditionally been viewed as an adaptive response triggered upon accumulation of unfolded proteins in the endoplasmic reticulum (ER), aimed at restoring ER function. The UPR can also be an anticipatory response that is activated well before the disruption of protein homeostasis. UPR signaling intersects at many levels with the innate and adaptive immune response. In some immune cell types like dendritic cells and B cells, particular UPR sensors appear constitutively acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
204
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(208 citation statements)
references
References 140 publications
(215 reference statements)
4
204
0
Order By: Relevance
“…Physiologically, XBP1 is necessary for differentiation of B cells, NK cells, and macrophages, although there is no detected basal IRE-1 activity for naive T cells and monocytes from spleen (17). There are only sporadic data on neutrophils (21), and in our study we found that .…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Physiologically, XBP1 is necessary for differentiation of B cells, NK cells, and macrophages, although there is no detected basal IRE-1 activity for naive T cells and monocytes from spleen (17). There are only sporadic data on neutrophils (21), and in our study we found that .…”
Section: Discussionmentioning
confidence: 45%
“…The proximal "sensors" of ER stress are the chaperone grp78 (also known as BiP) along with protein kinase R-like ER kinase (PERK), activating transcription factor (ATF)6, and inositol-requiring kinase 1 (IRE1), as well as their downstream transcriptional effectors ATF4, ATF6, and X-boxbinding protein 1 (XBP1)s, respectively (17,18). As part of normal cellular housekeeping, a complex molecular network has evolved to promote the proper folding of proteins and to identify and degrade misfolded proteins.…”
mentioning
confidence: 99%
“…These include ER stress-induced transcription factor CHOP, crucial for BMDDC IL-23 expression (12), and XBP1, essential for survival of plasmacytoid and conventional DC (23). Activation of the UPR is not limited to an overload in protein folding capacity and, in fact, alternative ways to trigger ER stress sensors exist but are not well understood (24,62). In vivo studies show that constitutive activation of the IRE-1 pathways is present in CD8a+ DC as well as developing B and T cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…While Rab11a activity recruits and keeps MHC-I within endosomal recycling compartment (ERC) under steady condition, MyD88-dependent TLR signals drive IKK2-mediated phosphorylation of phagosome-associated SNAP23, orchestrating ERC-phagosome fusion, promoting enrichment of phagosomes with ERC-derived MHC-I, and finally allowing cross-presentation during infection. 139 Transcription factor TFEB, 140 cell stress sensor IRE-1α, [141][142][143] NF-κB-inducing kinase (NIK) 144 and the lectin Siglec-G 145 have been shown to regulate DC cross-presentation in initiating antigen-specific CTL responses via distinct molecular mechanisms. For example, Siglec-G inhibits cross-presentation by CD8α+ DC via impairing the formation of the MHC class I-exogenous antigen peptide complex, contributing to suppression of CTL responses to intracellular bacterial infection with Listeria monocytogenes or Mycobacterium bovis bacillus Calmette-Guérin and tumors.…”
Section: Dendritic Cellsmentioning
confidence: 99%